Validity and Reliability of Periodontal Parameters Measurements (Medical Forum Monthly, 2021)
Objective: The purpose of this study was to evaluate the validity and reliability of periodontal parameters measurements.Study Design: Cross-sectional StudyPlace and Duration of Study: This study was conducted at the periodontology Khyber college of Dentistry Peshawar Pakistan from January 2020 to March 2020 for a period of 03 months.Materials and Methods: A total of 10 patients with 288 variables for five different periodontal parameters were examined. The study inclusion and exclusion criteria were followed. Two investigators (A and B) carried out the whole process. ‘A’ was the principal investigator/ intra examiner who measured the periodontal parameters and ‘B’ Co-investigator recorded all the readings. Five periodontal parameters including Pocket depth (PD), gingival recession (GR), bleeding on probing (BOP), plaque and calculus were measured.Results: Pocket depth and gingival recession were recorded as numeric data so ICC (Intra class correlation coefficient) was carried out for these variables whereas Kappa score was carried out for categorical data (BOP, plaque and calculus). The ICC and Kappa values were statistically significant and were in the range of strong correlation for intra examiner.Conclusion: The reproducibility recorded for calculus score and gingival recessions was 100%, 97% for plaque score, 95% for pocket depth measurement, and 91% for bleeding on probing and were statistically significant but it requires training and calibration with inter examiner.